Targeting of BCR-ABL: Lessons learned from BCR-ABL inhibition - Lin, X.; Qureshi, M. Z.; Attar, R.; Khalid, S.; Tahir, F.; Yaqub, A.; Aslam, A.; Yaylim, I.; de Carlos Back, L. K.; Farooqi, A. A.; Ismail, M. (Cellular and Molecular Biology, 2016)
In 1960 researchers reported that balanced translocation between chromosomes 22 and 9 resulted in the generation of Philadelphia chromosome. This breakthrough revolutionized our knowledge related to leukemia biology and contemporary studies revealed that chromosomal translocation resulted in the fusion between the 5"² segment of BCR gene and 3"² segment of the ABL gene to form BCR/ABL fusion gene. Research over the years has progressively and systematically improved our understanding of the genetic and proteomic basis of Leukemia. Genome-wide profiling studies, including genome sequencing and microarray analysis, have helped us in identification of different intracellular signaling cascades that are frequently mutated in Leukemia.  We partition this multi-component review into different sections related to biochemical characteristics of BCR-ABL+ cells, underlying mechanism of generation of mutations and crosstalk of BCR-ABL with various intracellular signaling cascades. We also summarize how BCR-ABL encoding mRNA is negatively regulated by different miRNAs and the strategies which are currently being used to effectively target BCR-ABL protein. We also provide an overview of the natural products which have been used for targeting of BCR-ABL protein. Better understanding of the protein network of Philadelphia positive leukemic cells will prove to be helpful in getting a step closer to personalized medicine.